THE TESTING OF THE VIETNAMESE RICE SAMPLES IN THE ROSTOV REGION - P. I. Kostylev; Е. V. Krasnova; А. V. Aksenov (Зерновое хозяйство России)
Rice (Oryza sativa L.) is one of the most important food crops in the world. The development of rice varieties for the conditions of Russia and especially the Rostov region requires a thorough study and introduction of the polymorphic gene pool for breeding work. The purpose of this study was to study comprehensively 45 collection Vietnamese rice samples (AGI), to estimate some of the key traits, and to select the best forms for breeding stress-resistant rice crops. These samples show a wide range of resistance to blast disease, bacteriosis, pests, lodging, salinization and flooding. The study was carried out in the Proletarsky district of the Rostov region. The standard varieties were the varieties “Boyarin” and “Yuzhanin” of ARC “Donskoy”. The study of the collection tropical rice gene pool according to a number of important economic and biological quantitative traits identified significant polymorphism. The vegetation period “sproutsflowering” varied from 85 to 142 days. All samples had a modern low-growing habit of plants with vertical rigid leaves and long drooping panicles (17.3–24.3 cm). Plant height ranged from 61.7 cm to 90 cm. Grains are long (9–10 mm), narrow (2–3 mm), with a weight to 29 mg, often with aroma. There was established a positive correlation between plant height and such traits as “kernel weight per panicle”, “1000 kernel weight”, “number of heavy kernels per panicle” and “fertility”. Kernel weight per panicle also correlated with the above-listed traits. Nine rice forms resistant to stress factors and well adapted to the region conditions have been selected for the breeding process. There has been carried out hybridization of the samples “OM 1401”, “OM 6106”, “OM 6561” with the local early ripening variety “Kontrakt”.